Tulathromycin – a semi-synthetic macrolidе antibiotic. II. Usage in veterinary medicine. - D. Mladenov; S. Yordanov; A. Dimitrova (Bulgarian Journal of Veterinary Medicine, 2023)
This article presents the results of studies on the use of the new macrolide antibiotic tulathromycin in veterinary medicine. The information is presented according to the species of domestic animals, dis-eases, doses and shemes for therapy and metaphylaxis. The first section includes data for cattle and calves affected by respiratory diseases, caused by M. haemolytica, M. bovis, H. somni and P. multo-cida, and keratoconjunctivitis caused by M. bovis. The second one shows data for swine and pigs affected by the respiratory pathogens A. pleuropneumoniae, P. multocida, H. parasuis, B. bronhisep-tica and M. hyopneumoniae. A third group presents information about small ruminants with mani-fested respiratory diseases caused by M. haemolytica, P. multocida, Mycoplasma spp., Pseudomonas spp. and hoof diseases from Dehelobacter nodosus. Fourth group includes the first test results of Rhodococcus equi, Streptococcus zooepidemicus, Theileria equi, Babesia bovis and Babesia bigemina, causing diseases in horses. The fifth section includes reports of treated rabbits most com-monly suffering from P. multocida respiratory infections. Finally, data from new studies on the use of tulathromycin in exotic animals and cases of some tropical diseases are listed. The provided informa-tion gives proof for the high sensitivity of the tested pathogens to tulathromycin and high clinical and economical effect that is efficient in single dose of 2.5 mg/kg. Compared to other antibacterial agents there is no resistance according to data available so far. Local accumulation and prolonged persis-tence of the drug in lung tissues, that result in a treatment regime with a single low-volume dose (2.5 mg/kg), are associated with positive clinical outcome in domestic animals: large ruminants, pigs, small ruminants and rabbits with respiratory diseases caused by M. haemolytica, H. somni, P. multo-cida and M. bovis; A. pleuropneumoniae, B. bronchiseptica, P. multocida, H. parasuis and M. hyopneumoniae; S.aureus, C. pseudotuberculosis and Streptococcus spp. and P.multocida.